Hyaluronic acid-functionalized bilosomes for targeted delivery of tripterine to inflamed area with enhancive therapy on arthritis. (1st January 2019) - Yang, Hailing; Liu, Zhenjie; Song, Yonglong; Hu, Changjiang
Abstract: Arthritis treatment has been challenging because of low drug exposure to the articular cavity. This study was intended to develop hyaluronic acid (HA)-functionalized bilosomes for targeted delivery of tripterine (Tri), an antiphlogistic phytomedicine, to the inflamed joint via ligand-receptor interaction. Tri-loaded bilosomes (Tri-BLs) with cationic lipid (DOTAP) were prepared by a thin film hydration method followed by HA coating to form HA@Tri-BLs. HA@Tri-BLs were then characterized by particle size ( PS ), entrapment efficiency ( EE ), and structural morphology. The in vitro drug release, hemocompatibility test and cellular uptake were performed to examine the formulation performances of HA@Tri-BLs. The in vivo pharmacokinetics and antiarthritic efficacy were evaluated in arthritic models, respectively. The obtained HA@Tri-BLs possessed a PS of 118.5 nm around with an EE of 99.56%. HA@Tri-BLs exhibited excellent cellular uptake and targeted delivery efficiency for Tri, which resulted in elongation of circulatory residence time and enhancement of intra-arthritic bioavailability (799.9% relative to Tri solution). The in vivo antiarthritic efficacy of HA@Tri-BLs was also significantly superior to uncoated Tri-BLs that gave rise to obvious inflammation resolution. Our findings suggest that HA-functionalized bilosomes are a promising vehicle for articular delivery of antiphlogistic drugs to potentiate their efficacy.